Drop Everything and Read: An Assessment of Students’ Reading Habits and Comprehension - Dy, Haydee Claire B.; Manalastas, Jared P. (Journal of Cultural Analysis and Social Change, 2025)
Reading is one of the macro skills in English that is a target for enhancement in the Purposive Communication English course in college. This is a fundamental skill for students’ academic success, personal development, and lifelong learning. To motivate more students to read, the Drop Everything and Read Program has been implemented by the English College professors of Lyceum of the Philippines University, Manila. This study employed a descriptive correlational design to assess the reading habits and reading comprehension of 418 college students enrolled in a Purposive Communication course. This program increased the utilization of books in the library and incorporates a book report requirement. Students have been required to choose a book related to their course and submit a book report, accompanied by a corresponding template, in which they write about the insights gained and reflections. The Revised Bloom’s Taxonomy guided the comprehension assessment. Based on the results, students' reading engagement and library visitation increased because it is part of the school’s requirement. It was revealed that without the requirement, students are not captivated by reading lengthy materials because they read according to their interests. These findings indicated that the Drop Everything and Read program of the Department of Languages and Humanities increased the students’ value of reading habits and comprehension. This implies that students appreciated the program in expanding their knowledge to the degree they have taken, improving their vocabulary and reading skills, and reading not only in their interest but as an accomplishment for professional development.